Identificação tipológica de processos judiciais: um caso de cultura de sigilo versus cultura de acesso - Souza Neto, Manoel Pedro de (2016)
Since the enactment of the Federal Law No. 11,419 of December 19, 2006, the Brazilian Courts, within each branch of justice, began scanning physical processes becoming digitized and those born-digital processes. In this context, problems of all kinds can arise in complex mission involving the electronic judicial process. Thus, it is necessary the implementation of procedures, methods and techniques to resolve such issues. Seeks, in this research, discuss the typological identification in the context of electronic lawsuits. Therefore, there was the identification of document types, using as a basic parameter produced the court process, received and accumulated by the Judicial Automation System (SAJ), developed by the Company Softplan / POLIGRAPH for the automation of the Brazilian Justice. Presents through the literature review, the issues facing the archival document, diplomatic, document type, chain of custody, normative acts issued by the CNJ and current legislation, which substantiated the best practices of computerization. Equally and aim to base the research were also discussed references concerning the concepts of culture, heritage and memory associated with documentary heritage archival and archival theory and methodology subsidy. The research is of applied nature, with a descriptive qualitative approach. The study is exploratory, analytical and descriptive and literature search. It was identified in the analysis and discussion of the results non-compliance with all safety requirements aimed at automation systems for the Brazilian judiciary and urgency in the implementation of the list of requirements recommended by the Model Requirements for Systems Computerized Processes and Document Management the Brazilian Judiciary (MoReq-Jus). Finally, there was the identification of document types aiming to discuss the culture of secrecy versus access culture. That said, there was the need to perform the analysis of the set of documents aimed at normalizing the typological identification and procedures for the management, preservation and continuous access to digital archival documents - electronic lawsuits - the Amazonas State Court